1996
DOI: 10.1097/00005537-199612000-00017
|View full text |Cite
|
Sign up to set email alerts
|

Laser‐Assisted Uvulopalatoplasty With Nd:YAG Laser for Sleep Disorders

Abstract: We evaluated the apnea index (AI), the oxygen saturation above 95% (SA95), the lowest oxygen saturation (LSAT), and snoring before and after laser-assisted uvulopalatoplasty (LAUP) in 106 patients with obstructive sleep apnea syndrome (n=59) or snoring (n=47). Type 1 LAUP was performed in 42 patients and type 2 LAUP in 64 patients. A 50% or greater reduction in AI was observed in 15 patients (35.7%) who underwent type 1 LAUP and 37 patients (57.8%) who underwent type 2 LAUP. Snoring was diminished in 18 (51.4%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 11 publications
1
11
0
Order By: Relevance
“…Of 5 patients with mild OSA, 3 (60%) achieved a postoperative RDI of Յ10. Four (80%) of these 5 met the criteria for surgical response as defined by Sher et al 9 Hanada et al 5 provided AI data only for 59 patients with OSA who underwent LAUP with a Nd:YAG laser (all other authors used a carbon dioxide laser), using 1 of 2 techniques. The response rate (defined as Ն50% reduction in AI) could be ascertained only for the 51 patients who underwent the second of the 2 techniques (in which more aggressive tissue removal was performed).…”
Section: Promentioning
confidence: 99%
See 1 more Smart Citation
“…Of 5 patients with mild OSA, 3 (60%) achieved a postoperative RDI of Յ10. Four (80%) of these 5 met the criteria for surgical response as defined by Sher et al 9 Hanada et al 5 provided AI data only for 59 patients with OSA who underwent LAUP with a Nd:YAG laser (all other authors used a carbon dioxide laser), using 1 of 2 techniques. The response rate (defined as Ն50% reduction in AI) could be ascertained only for the 51 patients who underwent the second of the 2 techniques (in which more aggressive tissue removal was performed).…”
Section: Promentioning
confidence: 99%
“…However,datafromtheauthorwhoreported the largest series (63 patients) with the greatest response rate (87%) were also not incorporated. Furthermore, no RDI data 5 or AI data 2 were available for some reports, potentially lowering the success rates, since the criteria described by Sher et al 9 allow a response based on either of these indices.…”
Section: Bottom Linementioning
confidence: 99%
“…Candidiasis, dysgeusia, and dysosmia occurred in fewer than 1% of cases. Reviewing the literature revealed four studies that explicitly reported no complications occurred for the 174 patients in those studies 8,14,20,34. Another study reported that the only complication or side effect was pain 9…”
Section: Resultsmentioning
confidence: 99%
“…Like other palatal snoring surgeries, snoring may recur over time. 6 This must be considered when counseling patients. Our data support those of others in noting that surgery failures may continue to occur long after surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, disadvantages of this technique include the need for and compliance with multiple‐stage operations and an expensive laser system. Long‐term success rates are similar to those for UPPP 6 . Radiofrequency ablation (RFA) of the soft palate has gained recent popularity as a new office technique to diminish excessive snoring.…”
mentioning
confidence: 90%